A Study on microwave - assisted extraction of patchouli essential oil : effect of hexane as solvent - Leong, Nguk Foong (2008)
The objective of this research was to extract patchouli essential oil with microwave assisted extraction (MAE) by using hexane as solvent extraction. This research focuses on effect of varying microwave power at 300 W, 400 W and 500 W at different time of extraction and influence of dielectric properties on extraction of patchouli oil. Hexane was used because it is a good extraction solvent Patchouli or Pogostemon cablin accumulates large amounts of essential oil. Patchouli oil contains sesquiterpene alcohols as its main active component or also known as patchoulol. In this research, the methods used were drying, grinding, extraction, separation and analysis. From the research, the optimum yield of patchoulol was 82.166% at microwave power 400 W and time extraction of 10 minutes and the major components of Pogostemon Cablin were patchoulol, α-bulnesene, α-guaiene and β-patchoulene.-Author